2014
DOI: 10.1371/journal.pone.0103607
|View full text |Cite
|
Sign up to set email alerts
|

Elevated mRNA-Levels of Gonadotropin-Releasing Hormone and Its Receptor in Plaque-Bearing Alzheimer's Disease Transgenic Mice

Abstract: Research on Alzheimer's disease (AD) has indicated an association between hormones of the hypothalamic–pituitary–gonadal (HPG) axis and cognitive senescence, indicating that post meno-/andropausal changes in HPG axis hormones are implicated in the neuropathology of AD. Studies of transgenic mice with AD pathologies have led to improved understanding of the pathophysiological processes underlying AD. The aims of this study were to explore whether mRNA-levels of gonadotropin-releasing hormone (Gnrh) and its rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…The HPG axis is regulated precisely by GnRH which plays a central role in both the reproductive functions and general hormonal control. Although the concentration of circulating GnRH is very low due to its short half-life, it is a prime factor in the pathogenesis of AD [43]. It is reported that GnRH induces adult neurogenesis in several brain regions typically afflicted by AD neuropathology [40].…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 99%
“…The HPG axis is regulated precisely by GnRH which plays a central role in both the reproductive functions and general hormonal control. Although the concentration of circulating GnRH is very low due to its short half-life, it is a prime factor in the pathogenesis of AD [43]. It is reported that GnRH induces adult neurogenesis in several brain regions typically afflicted by AD neuropathology [40].…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 99%
“…Interestingly, at least one other AD mouse model presumably has elevated levels of GnRH and LH. Recently, it was found that tgArcSwe mice, which carry two prominent AβPP mutations, have elevated mRNA levels of both GnRH and GnRH receptors (Nuruddin et al, 2014). Although LH was not measured, it is likely that it was increased because GnRH was increased.…”
Section: Role Of Lh In Alzheimer's Disease Pathology -Rodent Modelsmentioning
confidence: 99%
“…40 More recently, it has been reported a higher hippocampal level of GnRH and GnRHR mRNA in both male and female plaque-bearing AD transgenic mice (tgArcSwe), respect to age matched controls. 41 The treatment of these animals with the GnRHa leuprolide caused sex-related significant down-regulation of the expression of both the peptide and of its receptor, even though without significant changes in the plaque load; this may be suggestive of an insufficient effect of GnRHR activation in a more severe and advanced stage of the disease or an effect of GnRHa weaker than the transgene phenotype of the animal model. 41 Finally, clinical trials using leuprolide acetate has been shown to stabilize cognition in women with mild-to-moderate AD.…”
Section: -32mentioning
confidence: 97%
“…41 The treatment of these animals with the GnRHa leuprolide caused sex-related significant down-regulation of the expression of both the peptide and of its receptor, even though without significant changes in the plaque load; this may be suggestive of an insufficient effect of GnRHR activation in a more severe and advanced stage of the disease or an effect of GnRHa weaker than the transgene phenotype of the animal model. 41 Finally, clinical trials using leuprolide acetate has been shown to stabilize cognition in women with mild-to-moderate AD. 42 These findings clearly support the role of GnRH as a potential regulator of AD pathogenesis and lead to view the hypothalamic GnRH-NF-kB axis as an interesting mediator of aging-related neurodegenerative processes.…”
Section: -32mentioning
confidence: 97%
See 1 more Smart Citation